1995
DOI: 10.1046/j.1471-4159.1995.64020475.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrovirus‐Mediated Expression of an Artificial β‐Endorphin Precursor in Primary Fibroblasts

Abstract: Peptides are of potential interest in the field of gene therapy but require modification by genetic engineering to facilitate their secretion. Amino terminal addition of a signal peptide is not always sufficient to achieve this goal, as found in this study for β‐endorphin. To overcome this problem, addition of the pre‐pro‐sequence of mouse nerve growth factor to β‐endorphin was tested. Retrovirus‐mediated expression of a hybrid construct of the pre‐pro‐sequence of nerve growth factor and human β‐endorphin in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…First, HuMOR transduction of the afferent sensory nerve fibers innervating the TMJ, and the subsequent overexpression of MOR along the peripheral and central nerve axons and in the cell body, may be linked to the observed amelioration of joint pain. Previous studies have shown similar results following the injection of viral vectors encoding HuMOR directly into nerve trunks or sensory ganglia in combination with the exogenous administration of opioids (26)(27)(28)(29)(30)(31)(32)(33). However, in our experiments, there was no need for such opioid administration, since injection in the TMJ resulted in the induction of antinociception, presumably due to an interaction of the MOR with endogenous opioid ligands at the brainstem or within the joint.…”
Section: supporting
confidence: 80%
See 1 more Smart Citation
“…First, HuMOR transduction of the afferent sensory nerve fibers innervating the TMJ, and the subsequent overexpression of MOR along the peripheral and central nerve axons and in the cell body, may be linked to the observed amelioration of joint pain. Previous studies have shown similar results following the injection of viral vectors encoding HuMOR directly into nerve trunks or sensory ganglia in combination with the exogenous administration of opioids (26)(27)(28)(29)(30)(31)(32)(33). However, in our experiments, there was no need for such opioid administration, since injection in the TMJ resulted in the induction of antinociception, presumably due to an interaction of the MOR with endogenous opioid ligands at the brainstem or within the joint.…”
Section: supporting
confidence: 80%
“…Previous studies have shown that opioid precursor genes, such as enkephalins and ␤-endorphin or its receptors, can be successfully transferred to afferent sensory neurons via intrathecal administration as well as via direct injections into dorsal root ganglia or the sciatic nerve (26)(27)(28)(29)(30)(31)(32)(33). Those studies have demonstrated enhanced production of opioid peptides or receptors and a reduction of hyperalgesia in various nociceptive models.…”
mentioning
confidence: 99%
“…The mechanism of adenoviral gene transfer is more like cell transplantation studies which have been reported. For example, retrovirus vectors have been used to transfect and express ␤-endorphin in fibroblasts, 27 and spinal transplantation of adrenal medullary cells which naturally release opioid peptides reduces nocifensive behaviors (tail flick and paw pinch response) 28 and have been reported to decrease experienced pain in humans with pain and terminal cancer; 29 similar results have been demonstrated using the AtT-20 pituitary tumor-derived cell line modified to constitutively secrete enkephalin. 30,31 However, these approaches all rely on release of peptides into CSF, rather than localized release of enkephalin in the dorsal horn.…”
Section: Discussionmentioning
confidence: 68%
“…Beutler et al 13 demonstrated that addition of pre-pro-sequence of mouse nerve growth factor to beta-endorphin in primary fibroblast was necessary for the secretion of beta-endorphin. They showed that the pre-pro-sequence is cleaved from pre-pro-sequence/beta-endorphin construct before secretion, resulting in bona fide beta-endorphin.…”
Section: Discussionmentioning
confidence: 99%